Medicinal plants used by the Brunei community in Kampung Benoni, Papar Sabah / Abdul Manap Mahmud and Rafida Razali - Abdul Manap Mahmud; Rafida Razali (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
This study was carried out through a semi-structured interview with respondents via the 'snowballing' technique in Kampung Benoni, Papar, Sabah. There were about 43 species of medicinal plants found used by the Brunei community to treat 15 type of diseases. The findings of this study show that one plant was used to treat eye diseases; two plants were used to treat the otorhinolaryngologic disease; three plants were used to treat the stomatognathic disease; four plants were used to treat endocrine system diseases; six plants were used to treat skin diseases and substance-related disorders; eight plants were used to treat bacterial infections, mycoses, and viruses, musculoskeletal diseases, hemic and lymphatic diseases, pregnancy complications and female urogenital disease; nine plants were used to treat occupational diseases; 13 plants were used to treat digestive system diseases, immune system diseases and respiratory tract diseases; and 19 plants were used to treat wounds and injuries. The most common part of plants used in preparing herbal medicine is the leaves. The most common method of preparation is decoction and poultice. The plants came from 29 families. This study is helpful to assist us in recognising other potentials of the plants that can be used for medicinal purposes. The information in this paper will serve as baseline data for future phytochemical and pharmacological studies.